Proposal for collaborative research project between the Kenya Agricultural Research Institute and the International Livestock Centre for Africa - Solomon Bekure; Leeuw, P.N. de (International Livestock Centre for Africa, 1987)
A document prepared on the basis of past work conducted and discussions held by scientists of two institutions, ILCA & KARI (Kenya Agricultural Research Institute). It aims to provide background information that explains the nature of this project in order to facilitate preparation of specific research protocols for its implementation. It is presented in three parts. part I deals with the proposed collaborative research between the National Range Research Station (NRRS-KARI) and ILCA. Part II concerns the proposed collaborative research between the National Dryland Farming Research Station (NDFRS-KARI) and ILCA. Part III covers cooperation between KARI and ILCA in evaluation of cattle breeding policy and research in Kenya.